PROSEDUR HUKUM NATURALISASI KEWARGANEGAAN GANDA ARCANDRA TAHAR - Hamja, Hamja (Universitas Wiralodra, 2017)
The term citizenship is intended for citizens who already have their citizenship status, namely Indonesian Citizens, the vast territory of Indonesia is related to citizenship, many of which claim to be citizens, but in their citizenship status is unclear, even though in the positive Indonesian legal order Law No. 12 of 2006 states the conditions for someone to become an Indonesian citizen and that is not difficult. The purpose of this article is to report about the naturalization of legal procedures for dual citizenship related to the case experienced by Arcandra Tahar. Arcandra Tahar's citizenship case experienced by Arcandra Tahar is a unique case where each country has different rules and uses different principles to apply the rules of citizenship status in its country, Arcandra becomes an Indonesian citizen again after being dual citizenship. He became an Indonesian citizen through revelation and still wanted to become an Indonesian citizen and the submission of his American citizens' revocation.